RELATION BETWEEN DEFENSE BUDGET, PURCHASING POWER PARITY, FOREIGN EXCHANGE, AND EXTERNAL DEBT WITH MILITARY STRENGTH: EVIDENCE FROM ASEAN COUNTRIES - Syafril, Khairani; Saputro, Guntur Eko (JURNAL DARMA AGUNG, 2023)
Military strength plays a crucial role in ensuring the security, stability, and sovereignty of a nation. The objective of the study is to analyze the financial factors on military strength and provide evidence-based insights for policymakers and researchers in the field of defense and international relations. The research methodology employed in this study is a quantitative analysis using multiple linear regression. Data was collected from Global Firepower 2023’s website, and the statistical analysis was conducted using IBM SPSS 23. The findings reveal significant relationships between the financial factors and military strength in ASEAN countries. The defense budget was found to have the highest effect on military strength, indicating that allocating sufficient resources to defense expenditure is crucial for enhancing military capability. Moreover, foreign exchange was also found to have a significant impact, highlighting the importance of maintaining stable currency exchange rates for supporting defense capabilities. This research contributes to the existing literature by providing empirical evidence on the relationship between financial factors and military strength in the context of ASEAN countries. It adds to the understanding of the factors influencing military capabilities and offers insights for policymakers to make informed decisions regarding defense budget allocation and economic policies. Further research can explore additional variables and expand the sample size to enhance the generalizability of the findings. Overall, this study provides valuable insights into the complex interplay between financial factors and military strength, emphasizing the significance of economic policies and resource allocation for maintaining and enhancing national defense capabilities.